A Rumor of Anger: Understanding Muslims’ Voices in the Context of “Pure War” (American Journal of Islam and Society, 2006)
This paper is an attempt to understand “Muslims’ voices” at theadvent of the twenty-first century, especially the angry tonewithin. I would argue that such anger could be construed by situatingthe voices in the context of “pure war” constituted by terrorismused by different groups in the name of Islam, as well asstate violence used in the name of security and order at theexpense of rights and democracy. When the state exercises morecontrol over its population through modern technology, whichrenders private space almost obsolete, rumors are used to offsetits powerful gaze. Rumors about violence in the context of purewar, in turn, engender among Muslims some kinds of negativegroup cohesion that is fertile ground for anger directed against“the others,” as evidenced in Southeast Asia and elsewhere ...